CD226 (DNAM-1) is associated with susceptibility to juvenile idiopathic arthritis. Issue 12 (23rd July 2014) - Reinards, T H C M; Albers, H M; Brinkman, D M C; Kamphuis, S S M; van Rossum, M A J; Girschick, H J; Wouters, C; Hoppenreijs, E P A H; Saurenmann, R K; Hinks, A; Ellis, J A; Bakker, E; et al.
Abstract : Objectives: Juvenile idiopathic arthritis (JIA) is considered a complex genetic autoimmune disease. We investigated the association of genetic variants previously implicated in JIA, autoimmunity and/or immunoregulation, with susceptibility to JIA. Methods: A genetic association study was performed in 639 JIA patients and 1613 healthy controls of northwest European descent. Ninety-three single nucleotide polymorphisms (SNP) were genotyped in a candidate gene approach. Results of the entire JIA patient group (all subtypes) were compared with results obtained, alternatively, with a clinically homogeneous patient group including only oligoarticular and rheumatoid factor (RF) negative polyarticular JIA patients (n=493). Meta-analyses were performed for all SNPs that have been typed in other Caucasian JIA cohorts before. Results: SNPs in or near PTPN22, VTCN1, the IL2-IL21 region, ANKRD55 and TNFA were confirmed to be associated with JIA (p<0.05), strengthening the evidence for involvement of these genes in JIA. In the majority of these replicated SNPs, effect sizes were larger when analysing a homogeneous patient cohort than when analysing all subtypes. We identified two novel associations with oligoarticular and RF-negative polyarticular JIA: CD226 rs763361 (OR 1.30, 95% CI 1.12 to 1.51, p=0.0006) and CD28 rs1980422 (OR 1.29, 95% CI 1.07 to 1.55, p=0.008). Meta-analyses including reported studies confirmed the association of both SNPs with susceptibility to JIA (OR 1.16, p=0.001 and OR 1.18, p=0.001, for rs763361 and rs1980422, respectively). Conclusions: The CD226 gene has been identified as novel association with JIA, and a SNP near CD28 as a suggestive association. Both genes are probable candidate risk factors, since they are involved in costimulation of T cells.